Metformin Ameliorates D-Galactose-Induced Senescent Human Bone Marrow-Derived Mesenchymal Stem Cells by Enhancing Autophagy - Pingting Ye; Lei Feng; Dan Zhang; Ruihao Li; Yixuan Wen; Xiaohan Tong; Shuo Shi; Chunyan Dong (Stem Cells International)
Human bone marrow-derived mesenchymal stem cells (hBMSCs) are promising candidates for stem cell therapy in clinical trials. Applications of hBMSCs in clinical therapy are limited by cellular senescence due to long-term ex vivo expansion. Metformin, an oral hypoglycemic drug for type 2 diabetes, has been shown to have antiaging effects. However, the mechanisms of metformin in antiaging treatment remain controversial. Here, we used D-galactose (D-gal) to establish an appropriate model of senescent hBMSCs to explore the antiaging effects of metformin. Following metformin treatment with a low concentration range, senescence phenotypes induced by D-gal significantly changed, including generation of reactive oxygen species (ROS), loss of mitochondrial membrane potential (MMP), and cell cycle arrest. In contrast, no apparent change was found in unsenescent hBMSCs. Furthermore, the results show that activation of 5′AMP-activated protein kinase (AMPK) by metformin enhances cell autophagy in senescent hBMSCs. These findings suggest that metformin exerts antiaging function within the low concentration range by enhancing autophagy and exhibits potential benefits for clinical stem cell therapy by ameliorating the ex vivo replicative senescence of hBMSCs.